Value of 7T MRI and post‐processing in patients with nonlesional 3T MRI undergoing epilepsy presurgical evaluation. (19th September 2020) - Wang, Irene; Oh, Sehong; Blümcke, Ingmar; Coras, Roland; Krishnan, Balu; Kim, Sanghoon; McBride, Aaron; Grinenko, Olesya; Lin, Yicong; Overmyer, Margit; Aung, Tin Tun; Lowe, Mark; et al.
Abstract: Objective: Ultra‐high‐field 7‐Tesla (7T) magnetic resonance imaging (MRI) offers increased signal‐to‐noise and contrast‐to‐noise ratios, which may improve visualization of cortical malformations. We aim to assess the clinical value of in vivo structural 7T MRI and its post‐processing for the noninvasive identification of epileptic brain lesions in patients with pharmacoresistant epilepsy and nonlesional 3T MRI who are undergoing presurgical evaluation. Methods: Sixty‐seven patients were included who had nonlesional 3T MRI by official radiology report. Epilepsy protocols were used for the 3T and 7T acquisitions. Post‐processing of the 7T T1‐weighted magnetization‐prepared two rapid acquisition gradient echoes sequence was performed using the morphometric analysis program (MAP) with comparison to a normal database consisting of 50 healthy controls. Review of 7T was performed by an experienced board‐certified neuroradiologist and at the multimodal patient management conference. The clinical significance of 7T findings was assessed based on intracranial electroencephalography (ICEEG) ictal onset, surgery, postoperative seizure outcomes, and histopathology. Results: Unaided visual review of 7T detected previously unappreciated subtle lesions in 22% (15/67). When aided by 7T MAP, the total yield increased to 43% (29/67). The location of the 7T‐identified lesion was identical to or contained within the ICEEG ictal onset in 13 of 16 (81%). Complete resection of the 7T‐identified lesion was associated with seizure freedom ( P = .03). Histopathology of the 7T‐identified lesions encountered mainly focal cortical dysplasia (FCD). 7T MAP yielded 25% more lesions (6/24) than 3T MAP, and showed improved conspicuity in 46% (11/24). Significance: Our data suggest a major benefit of 7T with post‐processing for detecting subtle FCD lesions for patients with pharmacoresistant epilepsy and nonlesional 3T MRI.